2004
DOI: 10.1161/01.cir.0000105680.92873.70
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 as the Major Catalytic Component of an Endothelial NAD(P)H Oxidase

Abstract: Background-Recent evidence has suggested that reactive oxygen species are important signaling molecules in vascular cells and play a pivotal role in the development of vascular diseases. The activity of NAD(P)H oxidase has been identified as the major source of reactive oxygen species in vascular endothelial cells. However, the precise molecular structure and the mechanism of activation of the oxidase have remained poorly understood. Methods and Results-Here, we investigated the molecular identities and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
337
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(363 citation statements)
references
References 36 publications
21
337
1
4
Order By: Relevance
“…There have been a few studies on the expression of Nox family mRNAs and proteins in different kinds of human cells [15][16][17][18][19][20][21], but very few studies on the expression of Nox1 to Nox5 in the salivary glands even though it has been reported that salivary gland ducts express Duox1 [27]. platelet-derived growth factor induce the expression of Nox1 in vascular smooth muscle cells [28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few studies on the expression of Nox family mRNAs and proteins in different kinds of human cells [15][16][17][18][19][20][21], but very few studies on the expression of Nox1 to Nox5 in the salivary glands even though it has been reported that salivary gland ducts express Duox1 [27]. platelet-derived growth factor induce the expression of Nox1 in vascular smooth muscle cells [28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Nox2 (gp91 phox ) is predominantly expressed in phagocytes [15] and Nox3 exists in the inner ear of rodents, and is essential for the otoconium formation [18]. Nox4 is highly expressed in epithelial cells of renal tubules [19] and also in vascular endothelial cells [20]. Nox5 is predominantly expressed in the testis and spleen but its biological role is unknown [21].…”
Section: Introductionmentioning
confidence: 99%
“…The homologue Nox1 has been suggested to have a role in the host defense of epithelial cells (11) and to contribute to signaling leading to hypertrophy and angiogenesis and even tumor formation (7,12). Little is known about the functions of Nox4, but high expression of Nox4 has been suggested to induce senescence (8), and evidence indicates that Nox4 may also be involved in redox-mediated signal transduction in mesangial cells (13), adipocytes (14), and endothelial cells (15).…”
mentioning
confidence: 99%
“…NOX2 (previously named gp91phox) homologues (NOX1, 3, 4, 5, dual oxidase (DUOX)1 and DUOX2) have been characterised in different cell types, including vascular cells (4) . NOX1 and NOX4 are abundantly expressed in vascular smooth muscle cells and endothelial cells, respectively (6,7) . In contrast to phagocytic cells, vascular cells produce superoxide under basal, non-stimulated conditions but to a significantly lesser extent than phagocytes (8) .…”
mentioning
confidence: 99%